Promosi dan Harga terhadap Keputusan Pembelian - Faridah Faridah; Nurlina Nurlina; Retno Widowati (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study is to analyze the influence of promotions and prices on buying decisions at Traveloka Agents. This research method is descriptive quantitative. Interpretation of the data is processed using SPSS 25 statistics. The research model uses Multiple Regression Analysis to test the effect value of promotion (X1) and price (X2) on purchasing decisions. The analysis technique used is validity test, reliability test, and t-test and F-test. The results show that simultaneously there is an influence between promotion and price according to the correlation test with an R value of 0.440 or 44% in the medium category. This implies that the effect of variables X1 and X2 simultaneously on variable Y is 44%. Based on the T test, the results obtained are: a) the sig value of the promotion variable on purchasing decisions has a significant value of 0.499 > 0.05, and the value of t count < t table is 0.679 < 1.9916; b) the price variable on purchasing decisions has a significant value of 0.000 <0.05, and the t count > t table is 4.332 > 1.9916. Conclusion, a) there is no relationship between promotion variable and buying decision; b) there is an influence between price and purchase quality; c) Simultaneously, there is an influence between promotion and price with purchasing decisions, so it indicates the promotion given and the price is affordable and accepted by consumers. Keywords: Price, Purchase Decision, Promotion